Quantifying Water Quality and Economic Impacts of Fertilizer Workshops: A Case Study - Alexander Joseph Reisinger; Tina McIntyre (EDIS)
The goal of this new 8-page document is to demonstrate a scientifically based approach to estimating the water quality and subsequent economic benefits of UF/IFAS Extension programming related to nutrient management in residential landscapes. It also provides a sample impact statement that could be used by UF/IFAS Extension Agents as they compile the effectiveness of their program(s). Written by Alexander J. Reisinger and Tina McIntyre and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/ss705